Keabsahan Tanda Tangan Elektronik Dalam Transaksi Berbasis Blockchain Berdasarkan Hukum di Indonesia dan Implikasinya - Joshua Suwandi (CV Rewang Rencang, 2025)
This study examines the legal validity of electronic signatures in blockchain-based transactions within the framework of applicable law in Indonesia. As the adoption of blockchain technology expands across various sectors, including finance, trade, and government, understanding the legal status of electronic signatures becomes increasingly critical. This research employs a qualitative approach, encompassing case studies and analysis of relevant legal documents, including Law No. 11 of 2008 on Information and Electronic Transactions (UU ITE). The findings aim to provide insights into the implications of electronic signatures in enhancing transaction security and legal compliance in the digital landscape.